2016
DOI: 10.1016/j.jand.2015.09.020
|View full text |Cite
|
Sign up to set email alerts
|

American Diet Quality: Where It Is, Where It Is Heading, and What It Could Be

Abstract: Background Diet quality is critically important to the prevention of many types of chronic disease. The Federal government provides recommendations for optimal diet quality through the Dietary Guidelines for Americans and sets benchmarks for progress towards these recommendations through the Healthy People objectives. Objective This analysis estimated recent trends in American diet quality and compared those trends to the quality of diets that would meet the Healthy People 2020 (HP2020) objectives and the 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
87
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 12 publications
4
87
1
Order By: Relevance
“…Recent studies utilizing NHANES data showed that whereas overall dietary quality remains poor, there have been improvements to the quality of diet in America. [26][27][28] The increase in sedentary lifestyle could in part be responsible, as there has been a documented increase in sedentary lifestyle. 11,12 Sedentary lifestyle has been shown to negatively affect insulin sensitivity 29 and increase the relative risk of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies utilizing NHANES data showed that whereas overall dietary quality remains poor, there have been improvements to the quality of diet in America. [26][27][28] The increase in sedentary lifestyle could in part be responsible, as there has been a documented increase in sedentary lifestyle. 11,12 Sedentary lifestyle has been shown to negatively affect insulin sensitivity 29 and increase the relative risk of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The multifactorial causes of obesity are well recognized, with diet and physical activity being the most proximal drivers of obesity (Bleich, Jones-Smith, Wolfson, Zhu, & Story, 2015). Despite recent findings showing a temporal improvement in diet quality among U.S. adults in recent years (Wilson, Reedy, & Krebs-Smith, 2016), African American adults did not increase their diet quality over time, demonstrating that disparities still exist among communities of color (Rehm, Peñalvo, Afshin, & Mozaffarian, 2016). …”
mentioning
confidence: 61%
“…While recent U.S. trends suggest that child energy intakes are declining (22), diet quality is improving (23) and obesity is reaching a plateau (1), much remains to be understood about what should be done to improve child nutrition for obesity prevention. To help inform community efforts, we examined CPPs in multiple ways and examined multiple dietary factors Maximum employment status ranked as follows: full-time, part-time, unemployed (including temporary layoff or leave of absence) and other (including retired, disabled, keeping house and student).…”
Section: Discussionmentioning
confidence: 99%